The Effect of Giving Warm Compress Using Hotpack on Increasing Body Temperature in Post-Operative Patients with Hypothermia in the Recovery Room - Syamsuddin, Fadli; Nurlia, Nurlia; Purwanto, Romdon; Mooduto, Nur’Ain (Journal La Medihealtico, 2025)
One of the complications that arise after anaesthesia is hypothermia. Induction of general anaesthesia will cause vasodilation. Measures to prevent hypothermia can be done with a non-pharmacological approach called the rewarming method. in this study, namely to determine whether there is an effect of giving warm compresses using hot packs on increasing body temperature in postoperative patients with hypothermia in the Recovery Room (RR) of Prof. Dr. Aloeisaboe Hospital, Gorontalo City. used in this research is quantitative research using this research design is Pre-experimental with a one-group pre-post test design approach, the number of samples in this study is the same as the population of 10 respondents. The results showed that there was an effect of giving warm compresses using hot packs on increasing body temperature in postoperative patients with hypothermia in the Recovery Room (RR) of Prof. Dr. H. Aloei Saboe Hospital Gorontalo City with a P-Velue of 0.000 (α < 0.005). It is hoped that it can add information about giving warm compresses using hot packs to increase body temperature in postoperative patients with hypothermia and participate in providing nursing actions for giving hot packs to patients experiencing postoperative hypothermia in accordance with the SOP.